The geology of Tugtutôq and neighbouring islands South Greenland, Part II. Nordmarkitic syenites and related alkaline rocks - Upton, Brian G. J. (Meddelelser om Grønland, 1964)
Among the Precambrian (Gardar) intrusions in the Tugtutôq area, syenitic rocks are abundantly represented. Quartz-bearing alkalic rocks were first intruded after the emplacement of a number of large gabbro dykes. Although early Gardar nepheline syenites occur on Tugtutôq, no post-gabbro undersaturated syenites occur within the area under discussion. Quartz syenites and their faster cooled equivalents occur either as ENE directed dykes or as ring-dykes and stocks within a late Gardar central complex. The earliest quartz syenite occurs as the central component in a composite sector of one of the large gabbro dykes. This was succeeded by multiple swarms of dykes with alkalic types ranging from ’rhomb porphyry’ microsyenite to comendite. Dyke intrusion was virtually at an end by the time of formation of the central ring-complex. The total petrographic range of the oversaturated alkalic rocks extends from ferroaugite-fayalite syenites with relatively calcic feldspar (ca. Or25,Ab66,An9) to highly acid riebeckite-bearing rock types. The various intrusions are considered to represent magma batches supplied, at irregular intervals, from a deep-seated syenite complex which was crystallising throughout the latter part of the Gardar period. The inferred sub-surface complex is taken to be closely comparable to the Gardar complexes exposed at Nunarssuit and Kungnat, and to have differentiated by process of crystal fractionation. By analogy with the Kûngnât complex the parental magma of the underlying magma chamber(s) is believed to have passed through a larvikitic stage. The perthosite stock which forms the latest major intrusion on Tugtutôq is thought to indicate a slight divergence from the general larvikite-nordmarkite-alkali granite differentiation sequence. The magmas of this main differentiation sequence changed in composition along a "thermal valley" close to that of the synthetic system Or-Ab-SiO2-H2O.